TIN generation and point-cloud compression for vehicle-based mobile mapping systems. Issue 4 (October 2015) - Masuda, Hiroshi; He, Jun
Abstract: The vehicle-based mobile mapping system (MMS) is effective for capturing dense 3D data of roads, roadside objects and buildings. Since discrete points are not convenient for many application systems, a triangulated irregular network (TIN) is often generated from point-clouds. However, TIN data require two or three times larger storage than point-clouds. If TIN models can be promptly generated while loading point-clouds, it would not be necessary to store huge TIN models on a hard disk. In this paper, we propose two efficient TIN generation methods according to types of laser scanners. One is the line-by-line TIN generation method, and the other is the GPS-time based method. These methods can quickly generate TIN models based on scan lines of laser scanners. In addition, we introduce a new compression method to reduce the loading time of point-clouds. Our compression method is also based on the scan lines of laser scanners. Since points captured by a MMS tend to be positioned on nearly straight lines, their data size can be significantly reduced by coding the second order differences.